2015
DOI: 10.1007/s10439-015-1336-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Structure of Support Surface Translations Drive the Temporal Structure of Postural Control During Standing

Abstract: A healthy biological system is characterized by a temporal structure that exhibits fractal properties and is highly complex. Unhealthy systems demonstrate lowered complexity and either greater or less predictability in the temporal structure of a time series. The purpose of this research was to determine if support surface translations with different temporal structures would affect the temporal structure of the center of pressure (COP) signal. Eight healthy young participants stood on a force platform that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…27 However, variability is increasingly considered to be a marker of health in biological systems. 28 Therefore, if movement shows such characteristics, the neural control of such variable patterns would also demonstrate variable characteristics and thereby characterize healthy posture as separate from pathologic posture. Hence, among patients with musculoskeletal impairments, presenting the variability of cortical activation alongside more traditional linear measures may provide greater understanding of the neural control mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, variability is increasingly considered to be a marker of health in biological systems. 28 Therefore, if movement shows such characteristics, the neural control of such variable patterns would also demonstrate variable characteristics and thereby characterize healthy posture as separate from pathologic posture. Hence, among patients with musculoskeletal impairments, presenting the variability of cortical activation alongside more traditional linear measures may provide greater understanding of the neural control mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cavanaugh et al 14 demonstrated that the temporal sequence of steps taken during customary ambulatory activity in a sample of community dwelling-older adults contained fractal properties. Rand et al 51 recently demonstrated that patterns of support surface translations with temporal characteristics of varying complexity differentially altered the COP signals of healthy adults. In the field of robotics, Wang and Ren 52 recently reported on the development of comfortably wearable, assistive technologies based on multifractal concepts that may dramatically diminish the motor learning curve for movement retraining using prosthetics and orthotics.…”
Section: Future Directionsmentioning
confidence: 99%
“…While the strength of LRC increased significantly in the 250 Hz/12 db, condition, it decreased significantly in the 250 Hz/17.5 db condition in comparison with the no stimulus condition. It has been shown previously that motor response can be directionally driven in a similar manner through structured auditory stimulation (Kaipust et al 2013; Hunt et al 2014) and structured support surface oscillations (Rand et al 2015). Those studies, through the use of entrainment to structured sensory stimuli, demonstrated the adaptive flexibility of the sensorimotor system to switch between task constraints that require shifts in the LRC of gait parameters.…”
Section: Discussionmentioning
confidence: 89%